100th Anniversary of Jules Bordet's Nobel Prize: Tribute to a Founding Father of Immunology - Cavaillon, Jean-Marc; Sansonetti, Philippe; Goldman, Michel (Frontiers in Immunology, 2019)
The 100th Anniversary of the Nobel Prize in Physiology or Medicine 1919 awarded to Jules Bordet offers the opportunity to underline the contributions of this Belgian doctor to the blooming of immunology at the end of the nineteenth century at the Institut Pasteur de Paris. It is also the occasion to emphasize his achievements as director of the Institut Pasteur du Brabant and professor at the Université libre de Bruxelles. Both in France and Belgium, he developed a holistic vision of immunology as a science at the crossroads of chemistry, physiology and microbiology.